Opinião da corte: colegialidade e fundamentação - André Garcia Leão Reis Valadares (2023)
This study discusses the improvement of the way the Brazilian Federal Supreme Court communicates its decisions in cases submitted to the general repercussion system. The research aims to analyze whether the current format of publication of judgments meets the objectives of the Constitution and procedural legislation, considering the concerns expressed by jurisdictions, academics and STF ministers. The traditional format of publication of judgments, in which the votes of the Justices are presented in series, has raised concerns about the rational and unified reconstruction of the court's argumentation. This difficulty stems, in part, from the seriatim form of presentation of the votes of the ministers, which allows the explanation of individual interpretations, but makes it difficult to extract the reasoning adopted for decision making. The problem is aggravated by the perception that collegiality in the STF is mitigated by what has been coined "eleven islands" and "ministrocracy", as well as by other factors such as the delay in the publication of decisions, composition of documents, size of judgments and style of text. The paper seeks to establish the role of the STF based on the Constitution, procedural legislation and the court's own interpretation. It presents models of the Court and the relationship between the way of making decisions and the institutional role of the court, emphasizing the changes promoted by Constitutional Amendment 45/2004 and the evolution of the STF's interpretation of the general repercussion. The research develops the foundations for a new proposal for the formatting of judgments on the merits in cases of general repercussion. Examples of collegiate decisions adopted by foreign apex courts are analyzed, such as the seriatim, per curiam and majority models. Issues related to the counting of votes and the publication of concurring and dissenting votes are also addressed. Finally, a new formatting of judgments in appeals submitted to general repercussion is proposed. Normative and practical aspects are examined, considering necessary adjustments to the legislation and the STF's internal regulations, as well as practical aspects related to physical and virtual trial sessions and the preparation of the document. It is hoped that this research will contribute to the solution of the identified problem, providing a clearer and more reasoned formatting of judgments, aligned with the assumptions established by the current guidance of the STF. The improvement in the form of communication of general repercussion decisions is of great importance for the legitimacy and performance of the Court, especially in a context where such decisions have an impact on the legal system and on individuals/litigants.